2006
DOI: 10.1095/biolreprod.106.052613
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Mitogen-Activated Protein Kinase in Luteinizing Hormone-Induced Differential Regulation of Steroidogenesis and Steroidogenic Gene Expression in Mural and Cumulus Granulosa Cells of Mouse Preovulatory Follicles1

Abstract: The LH surge induces the terminal differentiation and onset of luteinization in granulosa cells of preovulatory follicles, a process that involves the differential expression of genes essential for steroidogenesis and appears to be mediated by complex signaling pathways. The objective of this study was to investigate whether these processes that commonly occur in mural granulosa cells (MGCs) also occur in cumulus cells, and whether they are mediated by the mitogen-activated protein kinase (MAPK), specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 67 publications
4
53
1
Order By: Relevance
“…PI3K is one of the most relevant proteins that controls steroidogenesis (Moore et al, 2001;Shimada et al, 2003;Yu et al, 2005;Su et al, 2006;Ebeling et al, 2011) and has defined actions in the activation and survival of primordial follicles, and in the recruitment of follicles (Zheng et al, 2012). PI3K controls steroidogenesis, an effect that has been observed by using 100 μM of its inhibitor, LY294002, a dose used by Hoshino et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K is one of the most relevant proteins that controls steroidogenesis (Moore et al, 2001;Shimada et al, 2003;Yu et al, 2005;Su et al, 2006;Ebeling et al, 2011) and has defined actions in the activation and survival of primordial follicles, and in the recruitment of follicles (Zheng et al, 2012). PI3K controls steroidogenesis, an effect that has been observed by using 100 μM of its inhibitor, LY294002, a dose used by Hoshino et al (2004).…”
Section: Discussionmentioning
confidence: 99%
“…Another outcome of this study was that the level of STAR mRNA expression was maintained at a constant level during IVM and then decreased during the IVF period. An in vivo study performed by Su et al (2006) demonstrated the simultaneous and dramatic upregulation of STAR and CYP11A1 expression in mice COCs after the endogenous surge of luteinizing hormone (LH). During our in vitro experiments, only CYP11A1 expression was upregulated during the maturation process.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro CC expansion and the resumption of oocyte meiosis are blocked by adding progesterone synthesis inhibitors or receptor antagonists to the maturation medium (pig: Shimada & Terada 2002, Shimada et al 2004and cattle: Wang et al 2006. Like mural granulosa cells, CCs exhibit dramatic changes in steroidogenic gene expression and steroidogenesis during the preovulatory period in mice (Su et al 2006). The expression of CYP11A1 and STAR (encoding the cholesterol side chain cleavage cytochrome P450 and the StAR protein respectively) is induced by the gonadotropin surge whereas the expression of CYP19A1 encoding aromatase is inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators, including us, have already shown that the ERK1/2 pathway is a negative regulator of aromatase expression (Andric and Ascoli, 2006;McDonald et al, 2006;Su et al, 2006;Zeleznik et al, 2003). We have also shown that pharmacological inhibitors of the EGF network and ERK1/2 phosphorylation restore the ability of gonadotropins to induce aromatase expression in immature granulosa cells expressing a high density of receptors (Andric and Ascoli, 2006).…”
Section: Introductionmentioning
confidence: 54%